2020
DOI: 10.1111/dth.14354
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of 20% aluminum sesquichlorohydrate vs 20% aluminum chloride for the treatment of axillary hyperhidrosis: A randomized controlled trial

Abstract: This study evaluated the efficacy and tolerability of topical aluminum sesquichlorohydrate (AS) when compared to aluminum chloride (AC) as a treatment for primary axillary hyperhidrosis (PAH). Twenty subjects were included in this randomized, controlled, split-side 8-week study. All participants applied 20% AS and 20% AC lotions in their axillae (one treatment per axilla) every night for 2 weeks; next, the application was reduced to three times a week for 4 weeks. The assessment was performed using the sweatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A small scale randomized controlled study conducted in Taiwan to evaluate the efficacy and tolerability of topical aluminum sesquichlorohydrate when compared to aluminum chloride as a treatment for patients with primary axillary hyperhidrosis (n = 20), indicated that the mean response time was 1.14 weeks for both treatments. 13 The study conditions were different in our present study and the study conducted in Taiwan, and direct comparison is therefore limited; however, sofpironium is suggested to have early effectiveness for primary axillary hyperhidrosis, which is comparable to that of topical aluminum chloride.…”
Section: Dlqi Total Scorementioning
confidence: 53%
See 1 more Smart Citation
“…A small scale randomized controlled study conducted in Taiwan to evaluate the efficacy and tolerability of topical aluminum sesquichlorohydrate when compared to aluminum chloride as a treatment for patients with primary axillary hyperhidrosis (n = 20), indicated that the mean response time was 1.14 weeks for both treatments. 13 The study conditions were different in our present study and the study conducted in Taiwan, and direct comparison is therefore limited; however, sofpironium is suggested to have early effectiveness for primary axillary hyperhidrosis, which is comparable to that of topical aluminum chloride.…”
Section: Dlqi Total Scorementioning
confidence: 53%
“…The current Japanese guideline recommends that topical aluminum chloride should be used as a first‐line therapy for primary axillary hyperhidrosis; 1 however, topical aluminum chloride, which is the most common topical preparation for the treatment of hyperhidrosis, 12 has not been studied in randomized controlled studies with primary axillary hyperhidrosis patients in Japan, and is not covered by Japanese health insurance. A small scale randomized controlled study conducted in Taiwan to evaluate the efficacy and tolerability of topical aluminum sesquichlorohydrate when compared to aluminum chloride as a treatment for patients with primary axillary hyperhidrosis (n = 20), indicated that the mean response time was 1.14 weeks for both treatments 13 . The study conditions were different in our present study and the study conducted in Taiwan, and direct comparison is therefore limited; however, sofpironium is suggested to have early effectiveness for primary axillary hyperhidrosis, which is comparable to that of topical aluminum chloride.…”
Section: Discussionmentioning
confidence: 99%
“…Current therapeutic approaches for primary axillary HH involve topical, intradermal, systemic and device‐based treatments as well as surgery procedures 8,9 . In the EU, up to June 2022, the only topical formulations available were antiperspirants containing aluminium salts applied in high concentrations, but they commonly cause skin irritation and show limited effects, especially in severe PAHH 3,10,11 . The use of anticholinergic substances for topical treatment of HH has been under investigation for several decades, leading to the following approvals for primary HH: glycopyrrolate as pads (also known as glycopyrronium bromide [GPB]) in South Korea, (Sweatrol® pads) glycopyrronium tosylate (GPT) wipes in the United States (Qbrexza®) 12 and Japan (Rapifort®), 13 sofpironium bromide gel in Japan (ECCLOCK®) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In the EU, up to June 2022, the only topical formulations available were antiperspirants containing aluminium salts applied in high concentrations, but they commonly cause skin irritation and show limited effects, especially in severe PAHH. 3,10,11 The use of anticholinergic substances for topical treatment of HH has been under investigation for several decades, leading to the following approvals for primary HH: glycopyrrolate as pads (also known as glycopyrronium bromide [GPB]) in South Korea, (Sweatrol® pads) glycopyrronium tosylate (GPT) wipes in the United States (Qbrexza®) 12 and Japan (Rapifort®), 13 sofpironium bromide gel in Japan (ECCLOCK®). 14 Recently a cream with GPB was approved in several EU countries (Axhidrox®), and while the systemic administration of the anticholinergic substances is regularly accompanied by adverse events, the safety profile of topical administration is favourable.…”
mentioning
confidence: 99%
“…Topical treatment is the first recommendation because it is safe, cost-effective and non-invasive. Aluminum chloride can cause skin irritation due to formation of hydrochloric acid in the presence of water [ 6 ]. Oxybutynin, a small tertiary amine molecule, is well suited for use as a transdermal agent.…”
Section: Introductionmentioning
confidence: 99%